2022
DOI: 10.1155/2022/3033311
|View full text |Cite
|
Sign up to set email alerts
|

The Hypolipidemic Effect of Hawthorn Leaf Flavonoids through Modulating Lipid Metabolism and Gut Microbiota in Hyperlipidemic Rats

Abstract: Objective. The purpose of this study was to explore the potential mechanisms of the lipid-regulating effects and the effect on modulating the gut microbiota of hawthorn leaf flavonoids (HLF) in the high-fat diet-induced hyperlipidemic rats. Methods. The hypolipidemic effect of HLF was investigated in the high-fat diet-induced hyperlipidemic rats. The action targets of HLF in the treatment of hyperlipidemia were predicted by network pharmacology and KEGG enrichment bubble diagram, which were verified by the tes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 111 publications
0
7
0
Order By: Relevance
“…In addition, the relative abundance of Peptostreptococcaceae has been significantly and positively correlated with back-fat thickness ( Soares et al., 2021 ). In a study by Hu et al. (2022b) , the high-fat group exhibited a greater abundance of Collinsella in the gut compared to the control group ( Hu et al., 2022b ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, the relative abundance of Peptostreptococcaceae has been significantly and positively correlated with back-fat thickness ( Soares et al., 2021 ). In a study by Hu et al. (2022b) , the high-fat group exhibited a greater abundance of Collinsella in the gut compared to the control group ( Hu et al., 2022b ).…”
Section: Discussionmentioning
confidence: 99%
“…In a study by Hu et al. (2022b) , the high-fat group exhibited a greater abundance of Collinsella in the gut compared to the control group ( Hu et al., 2022b ). Another experiment revealed that relative weights of mesenteric white adipose tissue (mWAT), epididymal white adipose tissue (eWAT), and renal white adipose tissue (kWAT) were increased in mice related with low relative abundance of Ralstonia .…”
Section: Discussionmentioning
confidence: 99%
“…Flavonoids can promote the decomposition of cholesterol and triglyceride to improve liver function and lipid metabolism (Huiming et al, 2022;Lanlan et al, 2022). In order to evaluate the synergistic effects of polysaccharide and flavonoid, the hyperlipidemia model Clostridium is a large and important group of bacteria in Firmicutes, containing a variety of intestinal pathogenic bacteria, which can produce exotoxins and have strong toxic effects on both humans and animals (Kociolek & Gerding, 2016).…”
Section: Con Clus I On and Discussionmentioning
confidence: 99%
“…Edible fungi polysaccharides can improve lipid metabolism disorders mainly by inhibiting or promoting the expression of related lipid metabolism enzymes and related factors, improving the activity of bile acid synthesis, regulating intestinal flora, and alleviating oxidative stress reaction (Yin et al, 2020; Zhao et al, 2023). Flavonoids can promote the decomposition of cholesterol and triglyceride to improve liver function and lipid metabolism (Huiming et al, 2022; Lanlan et al, 2022). In order to evaluate the synergistic effects of polysaccharide and flavonoid, the hyperlipidemia model was established.…”
Section: Conclusion and Discussionmentioning
confidence: 99%
“…(P. cuspidatum) (28) and Crataegus pinnatifida Bunge (C. pinnatifida) as representative detoxifying and blood-activating herbs (29) , are known for their efficacy in blood activation and resolving stasis, clearing heat, and detoxification (30). Extensive evidence has shown that polydatin (31) or hawthorn flavonoids (32) could exert cardioprotective effects and alleviate metabolic disorders, partially via the gut microbiota. Previously, our team combined hawthorn to promote blood circulation and resolving blood stasis with P. cuspidatum to clear heat and detoxify (33), applied it to the treatment of acute coronary syndrome, and achieved great clinical efficacy (34).…”
Section: Introductionmentioning
confidence: 99%